Papular sarcoidosis of the knees. A frequent form of presentation of systemic sarcoidosis - Marcoval, Joaquim; Mañá, Juan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: In recent years we have observed with increasing frequency granulomatous papular lesions involving the knees, for which we proposed the term papular sarcoidosis of knees. Objectives: To evaluate the clinicopathological features of papular sarcoidosis of the knees. Methods: Patients with papular lesions of the knees and histopathologically sarcoid granulomas were included in the study. Systemic sarcoidosis was investigated in all cases. Clinical charts were retrospectively retrieved. Biopsy specimens were evaluated under polarized light to detect foreign bodies. Results: Fifty-three patients fulfilled inclusion criteria. In 36 cases systemic sarcoidosis was diagnosed and these cases were considered as papular sarcoidosis of the knees. Foreign particles were observed in 21 of these 36 patients. In only 9/36 patients did the activity of systemic disease persist over two years. In 17 cases sarcoidosis could not be demonstrated during follow-up. Conclusion: Papular sarcoidosis of the knees can be considered a relatively frequent form of cutaneous sarcoidosis usually present at the beginning of the disease that can be useful for the diagnosis of sarcoidosis. It is mainly observed in acute forms of sarcoidosis and can be considered a sign of good prognosis.